Respuestas

2012-04-27T03:45:27+02:00

 2\ln \left( {2x + 2} \right) = \ln \left( {1 + \frac{{12}} {{25}}x} \right) + 2\ln 10 \hfill \\ \Rightarrow \ln \left[ {\left( {2x + 2} \right)^2 } \right] = \ln \left( {1 + \frac{{12}} {{25}}x} \right) + \ln 10^2 \hfill \\

 \Rightarrow \ln \left[ {\left( {2x + 2} \right)^2 } \right] = \ln \left[ {100\left( {1 + \frac{{12}} {{25}}x} \right)} \right] \hfill \\ \Rightarrow \left( {2x + 2} \right)^2 = 100 + 48x \hfill \\ \Rightarrow 4x^2 + 8x + 4 = 100 + 48x \hfill \\ \Rightarrow 4x^2 - 40x - 96 = 0 \hfill \\ \Rightarrow x = - 2 \vee x = 12 \hfill \\

 

Pero como el argumento (lo de adentro) no puede ser negativo, se descarta la solución -2 y queda 12